2006
DOI: 10.1103/physreva.73.062102
|View full text |Cite
|
Sign up to set email alerts
|

Teaching the environment to control quantum systems

Abstract: A non-equilibrium, generally time-dependent, environment whose form is deduced by optimal learning control is shown to provide a means for incoherent manipulation of quantum systems. Incoherent control by the environment (ICE) can serve to steer a system from an initial state to a target state, either mixed or in some cases pure, by exploiting dissipative dynamics. Implementing ICE with either incoherent radiation or a gas as the control is explicitly considered, and the environmental control is characterized … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
114
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 17 publications
0
114
0
5
Order By: Relevance
“…In contrast to the natural expectation that incoherent forces will introduce deleterious effects toward achieving desired control [23], recent studies [24,25] have shown that controlled quantum dynamics can survive intense field noise and decoherence, and even cooperate with them under special circumstances [26]. For example, a suitably optimized environment, as a incoherent control force, was suggested as a supplement to coherent control to provide a general tool for selective manipulation of both the Hamiltonian and dissipative aspects of the system dynamics [27,28]. Optimal coherent control fields were shown to be capable of cooperating or fighting with quantum measurements, and the performance may be optimized to achieve more effective control of the quantum dynamics.…”
Section: Measurement In Quantum Controlmentioning
confidence: 99%
“…In contrast to the natural expectation that incoherent forces will introduce deleterious effects toward achieving desired control [23], recent studies [24,25] have shown that controlled quantum dynamics can survive intense field noise and decoherence, and even cooperate with them under special circumstances [26]. For example, a suitably optimized environment, as a incoherent control force, was suggested as a supplement to coherent control to provide a general tool for selective manipulation of both the Hamiltonian and dissipative aspects of the system dynamics [27,28]. Optimal coherent control fields were shown to be capable of cooperating or fighting with quantum measurements, and the performance may be optimized to achieve more effective control of the quantum dynamics.…”
Section: Measurement In Quantum Controlmentioning
confidence: 99%
“…Optimal control by a tailored non-equilibrium, and generally time-dependent, state of the surrounding environment has been addressed in the literature (see [20] for more details). The master equation for the system interacting with an environment, characterized by its distribution function n k (t) is given by 5) where the coefficients γ ω (t) 0 determine the transitions rates between energy levels with transition frequencies ω.…”
mentioning
confidence: 99%
“…The equation for a system that simultaneously interacts with an electromagnetic field (t) and an environment described by a function γ(t) 0 generally has the form [20]: 6) where H 0 is the Hamiltonian describing the coherent part of the dynamics, H ef f is the effective Hamiltonian describing the unitary part of the system-environment interaction and H 1 is the dipole moment operator describing the interaction between the system and the field (t).…”
mentioning
confidence: 99%
“…В п. 4 настоящей работы обсуждается использование мастер-уравне-ний, возникающих в пределах слабой связи и малой плотности, при изучении некогерентного управления открытыми квантовыми системами [19] и созда-нии универсальных отображений Крауса [20].…”
unclassified
“…LDL , и, как правило, стремится разрушить квантовую когерентность [19]. Физическим примером некогерентного управления явля-ется некогерентное излучение, для которого n k плотность числа фотонов с импульсом k. В кинематическом описании эволюция открытой квантовой системы под действием управления c определяется семейством отображений Крауса Φ t c , так что ρ(t) = Φ t c (ρ 0 ).…”
unclassified